Effectiveness of Psycho-Correctional Methods and Technologies in Work with Children who have Autism: Systematic Review - Bocheliuk, Vitalii; Shevtsov, Andrii; Pozdniakova, Olena; Panov, Mykyta; Zhadlenko, Iryna (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: Proper care for children with autism spectrum disorder can help reduce the difficulties faced by autistic people throughout their life. This fact causes the necessity to study the most effective therapy, teaching and development methods, social interaction skills, and emotional intelligence for children with autism. Objective: This article is aimed at identifying the most effective methods and technologies in working with children who have autism that was described in the scientific works and at revealing reasons and necessities for their more detailed study as well as possibilities to implement them. Methods: Using methods analysis, comparison and analogy, statistical method, and generalization, several publications dedicated to correction methods in work with children who have autism were selected. The most common correction methods were indicated and described according to efficacy and frequency. Results: A thorough review of research, publications, and available information on the Internet were conducted. The most effective methods and technologies in working with autistic children were identified, which included applied behavioral therapy, treatment and education of autistic and related communication-handicapped children, Floortime, parent-child interaction therapy, method Tomatis, and the program Son-rise. Recent intelligent technologies were also considered, particularly Smart Platforms for Research, intervention, and Neurodevelopmental growth, the use of virtual reality, and the program Empowered Brain technology. Conclusions: The authors emphasize the necessity of thorough psychodiagnostics and the formation of psycho-correctional tasks based on exclusively personal needs, symptoms of the disorder, and disease etiology. The analysis of modern psycho-correctional technologies leads to the conclusion that their effectiveness depends, first of all, on the correct expedient application in each particular case.